Między radością a smutkiem. O nadziei w poezji Nikołaja Karamzina - Dąbrowska, Magdalena (Studia Rossica Posnaniensia, 2023)
The paper presents the poems by Nikolay Karamzin (1766–1826), which refer to hope. They include the following groups of texts: 1) reflection poems: To myself (1795), The song (1795), The hope (1796), To an unfaithful (1796), Sorrow and joy (1797), The coast (1802); 2) occasional poems: about the Tsar Pavel I (1796), about G. Khovanski (1796) and about P. Pelski (1803); 3) poems touching upon the life of a poet and poetry: To a poor poet (1796) and The talents (1796). Some poems are autobiographical (The coast was written after the death of Karamzin’s first wife). The hope, which is based on a comparison of a human’s life to a journey, is considered the most meaningful of his texts. According to Karamzin, life is filled with joy and sorrow, expectation and disappointment, but hope makes the plans easier to achieve, and brings a man closer to the goal. The meaning of his poems is optimistic after all. Karamzin’s letters to Ivan Dmitriev, a poet and a friend, serve as an interpretive background in the article.